RETATRUTIDE IN INTERNAL MEDICINE: A NOVEL TRIPLE HORMONE RECEPTOR AGONIST FOR OBESITY, TYPE 2 DIABETES, AND CARDIOMETABOLIC RISK - Livia de Oliveira Cardoso; Anny Karollynny Batista de Oliveira Neves; Gabriel Matheus D’Abadia França; Larissa Eduarda Nascimento Paula; Stela Barbosa Zago; Marinaldo Soares Leite (International Journal of Science and Research Archive, 2026)
Obesity and type 2 diabetes mellitus are major chronic diseases associated with cardiovascular, metabolic, hepatic, and renal complications. The development of incretin-based therapies has substantially changed the management of these conditions. Retatrutide is a novel once-weekly triple hormone receptor agonist that simultaneously activates the glucose-dependent insulinotropic polypeptide (GIP), glucagon-like peptide-1 (GLP-1), and glucagon receptors. Unlike currently established incretin therapies, retatrutide combines incretin-mediated effects with glucagon receptor activation, potentially enhancing energy expenditure and lipid metabolism in addition to reducing appetite and food intake. This narrative review aimed to evaluate the current evidence regarding the efficacy, safety, metabolic effects, and potential clinical applications of retatrutide in internal medicine. A literature search was performed using PubMed/MEDLINE and major clinical trial and guideline publications, prioritizing randomized controlled trials, systematic reviews, meta-analyses, and contemporary publications available through August 2026. Phase 2 studies demonstrated substantial, dose-dependent weight loss in adults with obesity, with reductions approaching 24% after 48 weeks at the highest studied dose. In individuals with type 2 diabetes, retatrutide also produced clinically meaningful reductions in glycated hemoglobin and body weight. Improvements in lipid parameters, hepatic steatosis, and other cardiometabolic markers have also been reported. Gastrointestinal adverse events, particularly nausea, diarrhea, and vomiting, represent the most frequent treatment-related adverse effects and appear to be dose dependent. Cardiovascular, renal, and long-term safety outcomes remain under investigation. Recent phase 3 studies have expanded the evidence base, although retatrutide remains an investigational therapy and definitive long-term outcome data are still required. Retatrutide may represent a new generation of pharmacological treatment for obesity and metabolic disease, but its eventual place in clinical practice will depend on the results of ongoing cardiovascular, renal, and long-term safety trials.